EFEKTIVITAS MODEL PEMBELAJARAN TPS (THINK PAIR SHARE) BERBASIS KAHOOT TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 2 JATI AGUNG - Revi Zaira Zenifa; Chairul Anwar; Listiyani Siti Romlah (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study was motivated by the low academic achievement of students in the subjects of Islamic Religious Education and Character Education at SMP Negeri 2 Jati Agung. This issue is believed to be influenced by the use of learning models that lack variety and the suboptimal use of engaging learning media. Therefore, it is necessary to implement a learning model that can enhance student engagement and understanding, one of which is through the Kahoot-based Think Pair Share (TPS) learning model. This study aims to determine the effectiveness of the Kahoot-based TPS learning model on student learning outcomes, specifically on the cognitive indicators C4 (analyzing) and C5 (evaluating). The research method used is a quantitative approach with a quasi-experimental design of the post-test only control group type. The research subjects consisted of two eighth-grade classes, namely Class VIII-D as the control class and Class VIII-F as the experimental class, with a total of 60 students. Data collection was conducted through achievement tests, which were analyzed using a pooled variance t-test after conducting preliminary tests for normality and homogeneity. The results of the study indicate that there is a significant difference between the learning outcomes of students using the Kahoot-based Think Pair Share (TPS) learning model and those using conventional learning. This is evidenced by a p-value of 0.036 < 0.05. Thus, it can be concluded that the Kahoot-based Think Pair Share learning model has a significant effect on student learning outcomes in the subjects of Islamic Religious Education and Character Education.